Evaluation of offshore wind turbine blades coating thickness effect on leading edge protection system subject to rain erosion - Ansari, Quaiyum M.; Sánchez, Fernando; Mishnaevsky, Leon; Young, Trevor M. (Renewable energy, 2024)
During operation, wind turbine blades are subjected to a wide range of environmental and loading conditions and blade erosion can have a negative impact on performance and power production. The layer-wise thickness of a leading edge coating system can have a substantial effect on erosion rate due to rain droplet impact, which can result in a variety of complex failure modes, such as delamination of the coating-substrate interface. The objective of this work to develop single droplet numerical models to investigate the influence of elastic stress wave developments generated during impact. Following that, a single rain droplet FE parametric research was performed with different coating materials, coating and filler putty thicknesses. It is shown that stiffer coatings lead to higher stresses. Furthermore, thicker coatings can result in lower stress transfer to the filler material. The empirical equations developed for coating thickness and filler putty thickness were found to be in good agreement with each other. This detailed baseline investigation can help in understanding the effect of coating and filler putty thickness on rain erosion rate, as well as analysing different coating designs using empirical equations for the development of more durable leading edge protection coatings for wind turbine blade applications.